2022
DOI: 10.3390/jcm11236928
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Inpatient Cost of Hip Replacement? A Time-Driven Activity Based Costing Pilot Study in an Italian Public Hospital

Abstract: The emphasis on value-based payment models for primary total hip replacement (THA) results in a greater need for orthopaedic surgeons and hospitals to better understand actual costs and resource use. Time-Driven Activity-Based Costing (TDABC) is an innovative approach to measure expenses more accurately and address cost challenges. It estimates the quantity of time and the cost per unit of time of each resource (e.g., equipment and personnel) used across an episode of care. Our goal is to understand the true c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Although the literature on the post-operative risk of thromboembolic events documents an increasing risk in obesity, this is not consistently replicated in the orthopaedic literature [ 44 , 45 , 46 ]. Similarly, it has been empirically shown that the risk of dislocation increases with extreme excursions of the joint angle and fat tissues around the hip [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature on the post-operative risk of thromboembolic events documents an increasing risk in obesity, this is not consistently replicated in the orthopaedic literature [ 44 , 45 , 46 ]. Similarly, it has been empirically shown that the risk of dislocation increases with extreme excursions of the joint angle and fat tissues around the hip [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ao considerar tal índice, se faz uma simplificação do contexto produtivo do Centro de Diagnósticos por Imagens (CDI) abrangido. Portanto, é necessário um entendimento acurado da configuração e dos tempos das atividades inerentes como mecanismo para evitar (ou minimizar) a simplificação de medições a respeito, especialmente porque podem comprometer a qualidade informacional dos resultados, como mencionado por Thaker et al (2022), Fidanza et al (2022) e Bernstein et al (2023). No caso do Centro de Diagnóstico de Imagem (CDI) investigado, a estimativa de uso efetivo foi empregada como forma de descontar eventuais horas não trabalhadas, que no cotidiano do CDI costumam ocorrer por motivos diversos (intervalos para alimentação, paradas para ajustes ou manutenção de equipamentos, não comparecimento de pacientes etc.…”
Section: Análise Dos Resultadosunclassified
“…Ou seja, pode complementar as iniciativas gerenciais tradicionais de redução de gastos ao quantificar as etapas com custos mais elevados, o que facilita a priorização das iniciativas para reduzir gastos e melhorar a eficiência. Fidanza et al (2022) aduzem que o TDABC pode ser considerado uma abordagem inovadora para medir custos com maior precisão, pois estima a quantidade de tempo e o custo por unidade de tempo dos recursos utilizados durante um atendimento ou exame. Além disso, de acordo com Bernstein et al (2023), o TDABC proporciona um instrumento capaz de calcular os custos associados aos procedimentos médicos de modo mais preciso.…”
Section: Revisão Da Literaturaunclassified
“…Osteoarthritis (AO) is currently one of the most frequently diagnosed chronic diseases, affecting an estimated 10% of men and 18% of women over 60 years of age, and with the increase in life expectancy, both its prevalence and incidence are expected to rise. This condition is degenerative until the loss of function and disability leads to important healthcare and social costs [ 1 , 2 ]. In addition to chondral pathologies, skeletal diseases, such as nonunion and bone defects due to trauma, infections, or tumors, represent a great challenge for orthopedic surgeons.…”
Section: Introductionmentioning
confidence: 99%